"Bottom crystal" and possibility of water wave attenuation (Archives of Mechanics - Test, 2003)
The influence of periodic bottom structure ("bottom crystal") on surface water waves is considered. The problem reduces to a two-dimensional Helmholtz operator with periodic potential. Zero-range potential method based on the theory of self-adjoint extensions of symmetric operators is used. It is shown that there is a gap in the spectrum. An application of this spectral property to the problem of wave attenuation is discussed.